2015
DOI: 10.1016/j.bmcl.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

N-Oxide derivatives of 3-(3-pyridyl)-2-phosphonopropanoic acids as potential inhibitors of Rab geranylgeranylation

Abstract: The N-oxide derivatives of [2-(3-pyridinyl)-1-hydroxyethylidene-1,1-phosphonocarboxylic acid (or PEHPC) and [2-(3-pyridinyl)-1-ethylidene-1,1-phosphonocarboxylic acid (or PEPC) have been prepared and evaluated for their activity against several enzymes which utilize isoprenoids. The parent pyridines are known inhibitors of GGTase II, but the N-oxide derivatives show no improvement in biological activity in assays with the isolated enzyme. However, the PEHPC N-oxide did induce significant accumulation of intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…We found that other analogues of heterocyclic bisphosphonates show greater activity against RGGT than originally reported 3-PEHPC, while those derived from aminoalkyl BP are inactive . Oxidation of nitrogen in the pyridine ring of 3-PEHPC to N -oxide did not improve activity against RGGT . We demonstrated that the most active derivatives of currently known phosphonocarboxylates contain imidazo­[1,2- a ]­pyridine (3-IPEHPC and its analogues) , or the imidazole ring in their structure.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…We found that other analogues of heterocyclic bisphosphonates show greater activity against RGGT than originally reported 3-PEHPC, while those derived from aminoalkyl BP are inactive . Oxidation of nitrogen in the pyridine ring of 3-PEHPC to N -oxide did not improve activity against RGGT . We demonstrated that the most active derivatives of currently known phosphonocarboxylates contain imidazo­[1,2- a ]­pyridine (3-IPEHPC and its analogues) , or the imidazole ring in their structure.…”
Section: Introductionmentioning
confidence: 76%
“…22 Oxidation of nitrogen in the pyridine ring of 3-PEHPC to N-oxide, did not improve activity against RGGT. 23 We demonstrated that the most active derivatives of currently known phosphonocarboxylates contain imidazo [1,2-a]pyridine (3-IPEHPC and its analogs) 20,21 or the imidazole ring 22 in their structure.…”
mentioning
confidence: 99%
“…We hence propose that clinical usefulness of statins for cancer therapy should be reevaluated using the biomarkers that we have identified in this paper to be predictive of the responders of cancer cells. In addition to statins, GGT-II inhibitors that can be administered safely to humans may have high potential to be developed as cancer therapeutics ( Berndt et al, 2011 ; Zhou et al, 2015 ), although to date, the development of safe GGT-II inhibitors has been unsuccessful because of the serious side effects of the conventional method of GGT inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds were tested for biological activity by Dr. Sarah A. Holstein in an enzyme assay with GGTase II. 43 However, these N-oxide carboxyphosphonate derivatives of 3-PEHPC showed no improvement in potency when compared to 3-PEHPC. Retrosynthetically, the isoprene triazole carboxyphosphonate sodium salt 13, would be obtained via hydrolysis of the corresponding carboxyphosphonate ester 14 ( Figure 10).…”
Section: Hmg-mentioning
confidence: 96%
“…39 Therefore, to avoid unnecessary cellular effects, it would be advantageous to develop an enzyme inhibitor that targets downstream of FDPS to ultimately inhibit protein geranylgeranylation. The Wiemer group has prepared a number of non-nitrogenous bisphosphonates, 40,41 nitrogenous bisphosphonates, 42 and carboxyphosphonates 43 as shown in Figure 6. This is an indirect approach and might result in disruption of other cellular processes in the IBP upstream of GGTase II, such as the production of cholesterol.…”
Section: Hmg-mentioning
confidence: 99%